Association between glaucomatous optic disc and depressive symptoms independent of light exposure profiles: a cross-sectional study of the HEIJO-KYO cohort. Issue 8 (25th October 2018) - Yoshikawa, Tadanobu; Obayashi, Kenji; Miyata, Kimie; Ueda, Tetsuo; Kurumatani, Norio; Saeki, Keigo; Ogata, Nahoko
Abstract : Background: Glaucoma may cause physiological and behavioural circadian misalignment because of the loss of intrinsically photosensitive retinal ganglion cells, the primary receptors of environmental light. Although studies have suggested a high prevalence of depression in patients with glaucoma, it is unclear whether the association is independent of the light exposure profiles as an important confounding factor. Methods: In this cross-sectional study of a community-based cohort of 770 elderly individuals (mean age, 70.9 years), glaucomatous optic discs were assessed using fundus photographs and depressive symptoms were assessed using the short version of the Geriatric Depression Scale (GDS). Daytime and night-time ambient light exposures were objectively measured for 2 days. Results: Depressive symptoms (GDS score ≥6) were observed in 114 participants (prevalence, 14.8%) and glaucomatous optic discs were detected in 40 participants (prevalence, 5.2%). The prevalence of depressive symptoms was significantly higher in the group with glaucomatous optic disc than in the group without it (30.0% vs 14.0%, respectively; p=0.005). Multivariable logistic regression analysis adjusted for potential confounding factors, including daytime and night-time light exposures, revealed that the OR for depressive symptoms was significantly higher in the group with glaucomatous optic disc than in the group without it (OR 2.45, 95% CI 1.18 to 5.08; p=0.016). Conclusions: In this general elderly population, glaucomatous optic disc was significantly associated with higher prevalence of depressive symptoms independent of a number of potential confounding factors, including daily light exposure profiles.